An Unusual Case of Hypoproteinemia in Childhood: Keep in Mind Trichobezoar - Stinco, Mariangela; Montemaggi, Alessandra; Noccioli, Bruno; Resti, Massimo; Grosso, Salvatore; Trapani, Sandra (Frontiers in Pediatrics, 2020)
Protein-losing enteropathy (PLE) is a rare condition characterized by protein loss through the gastrointestinal tract, leading to hypo-proteinemia. Patients may be asymptomatic or present with variety of complications of hypoproteinemia (e.g. oedema, ascites, pleural and cardial effusions). We describe a case report of a young girl suffering from behavioural disorder since childhood who presented with generalised oedema, hypoproteinaemia and microcytic hypochromic anaemia. In addition, the girl had an intervention for jejunal atresia and intestinal malrotation in her past medical history. Upper gastrointestinal endoscopy revealed a trichobezoar extending from stomach into the small bowel, thus classified as Rapunzel Syndrome (RS), causing mechanical obstruction of intestinal lumen and intestinal lymphatic drainage resulting in a protein-losing enteropathy (PLE). Trichobezoar was successfully removed by a surgical laparotomy resulting in resolution of symptoms and normalisation of biochemical parameters. Possibly, previous surgery might have had an influence on intestinal dysmotility and trichobezoar formation. PLE is a very rare presenting symptom of RS, developing as result of intestinal obstruction caused by large trichobezoars. RS has to be considered in patients, especially adolescents, suffering from behaviour disorder as trichotillomania and trichophagia. Surgical removal and nutritional supplementation are the gold treatment of large trichobezoar.